2018
DOI: 10.1093/ajcn/nqy041
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber intervention on gut microbiota composition in healthy adults: a systematic review and meta-analysis

Abstract: Dietary fiber intervention, particularly involving fructans and galacto-oligosaccharides, leads to higher fecal abundance of Bifidobacterium and Lactobacillus spp. but does not affect α-diversity. Further research is required to better understand the role of individual fiber types on the growth of microbes and the overall gut microbial community. This review was registered at PROSPERO as CRD42016053101.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
341
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 490 publications
(372 citation statements)
references
References 154 publications
21
341
2
8
Order By: Relevance
“…Some, 58 but not all, 59 studies have shown that higher fiber intake enriches Lactobacillus spp. and butyrate-producing bacteria in the gut, such as Bifidobacterium, Clostridium, Anaerostipes, Eubacterium, and Roseburia species, and increases production of SCFAs.…”
Section: Fibermentioning
confidence: 99%
“…Some, 58 but not all, 59 studies have shown that higher fiber intake enriches Lactobacillus spp. and butyrate-producing bacteria in the gut, such as Bifidobacterium, Clostridium, Anaerostipes, Eubacterium, and Roseburia species, and increases production of SCFAs.…”
Section: Fibermentioning
confidence: 99%
“…There is abundant literature concerning the effects of dietary fibre on the growth of Bifidobacterium and Lactobacillus spp. (So et al, 2018), however dietary fibre can also stimulate other microbes.…”
Section: Furthermore Intestinal Bacteria Including Lactobacillus Andmentioning
confidence: 99%
“…Based on six RCTs that reported data suitable for inclusion in the meta‐analysis (investigating polydextrose, xylo‐oligosaccharide, polysaccharopeptide, arabinoxylans and a high‐fibre diet), fibre had no effect on α‐diversity compared with control (So et al . ). Of a further seven studies reporting α‐diversity that were not included in the main meta‐analysis, two reported increases in diversity after the consumption of resistant starch type 2 (Alfa et al .…”
Section: Microbial Fermentation Of Fibrementioning
confidence: 97%
“…So et al . () did not carry out subgroup analysis by fibre type and, at present, there are few studies that have measured the effect of prebiotics on microbial diversity. The net results of selective stimulation of beneficial species, the growth of which produces an unfavourable environment for pathogenic species due to the production of metabolites which reduce intestinal pH, and the stimulation of other species, may vary between individuals due to the baseline composition, prebiotic dose and wider composition of the diet; therefore, affects on diversity may be difficult to predict (Holscher ).
Diets higher in fibre are associated with a decreased risk of CVD, type 2 diabetes and colorectal cancer. RCTs demonstrate that fibre decreases transit time and increases faecal bulk, reducing constipation.
…”
Section: Microbial Fermentation Of Fibrementioning
confidence: 99%
See 1 more Smart Citation